Beyond subsumption and balancing: A critique of proportionality theory from the case of freedom of speech - Ribeiro, Caio Gentil (Universidade de Estado do Rio de Janeiro, 2019)
This article criticizes Robert Alexy’s Proportionality Theory. After describing the structure of such theory, the article addresses its use regarding freedom of speech; more precisely, it deals with the relations between freedom of speech and abusive advertising and between freedom of speech and financing of electoral campaigns. The criticisms to proportionality are drawn from Ronald Dworkin’s approach on how rights must be defined and from the method John Rawls uses to build his theory of justice, and stress how Alexy’s theory, despite its intended neutrality, is incompatible with these two substantive approaches. It is argued, then, that this incompatibility is the result of the presumption that there is no other form of legal reasoning besides the dichotomy subsumption/balancing. Finally, it is suggested that the use of proportionality as a way of justification undermines the legitimacy of law as a means of coercion.
Para além da subsunção e do sopesamento: Uma crítica à teoria da proporcionalidade a partir do caso da liberdade de expressão
Keywords: Alexy; Dworkin; Freedom of speech; Proportionality; Rawls